Cambridge English for Job-hunting - Downes C. Colm (Professional English)
Cambridge English for Job-hunting is for upper-intermediate to advanced level (B2-C1) learners of English who need to use English during the job application process. The course can be used in the classroom or for self-study. Ideal for working professionals and those new to the world of employment, the course develops the specialist language knowledge and communication skills that job-seekers need to apply for and secure jobs. Cambridge English for Job-hunting comprises six standalone units covering core areas such as preparing a CV, writing a cover letter and answering interview questions. By featuring authentic material such as CV's and letters, learners are given practical experience in preparing vital documentation.The course also features a special focus on the interview scenario, including extracts from interviews on the Audio CD. As well as familiarising learners with commonly asked interview questions, the course also develops more advanced interviewing techniques, such as answering difficult questions and selling yourself effectively. In addition, the course offers valuable advice to help build applicants' confidence. The online Teacher's Book has extensive background information, useful web links and extra printable activities. The course comprises: Student's Book with 2 Audio CDs. Teacher's Book online.